Effects of Phenolic-Rich Onion (Allium cepa L.) Extract on the Growth Performance, Behavior, Intestinal Histology, Amino Acid Digestibility, Antioxidant Activity, and the Immune Status of Broiler Chickens - Omar, Anaam E.; Al-Khalaifah, Hanan S.; Mohamed, Wafaa A. M.; Gharib, Heba S. A.; Osman, Ali; Al-Gabri, Naif A.; Amer, Shimaa A. (Frontiers in Veterinary Science, 2020)
The effect of phenolic-rich onion extract (PROE), as a feed additive, was evaluated on the growth, carcass traits, behavior, welfare, intestinal histology, amino acid ileal digestibility “AID%” and the immune status of broiler chicks, for 35 days. A total number of 400, one-day-old broiler chicks (45.38 g ±1.35) were allocated to four different treatments with ten replicates each (100 chicks/treatment) consisting of; T1: basal diet without additives (control treatment) (PROE0); T2: basal diet + onion extract (1 g/kg diet) (PROE1); T3: basal diet + onion extract (2 g/kg diet) (PROE2); and T4: basal diet + onion extract (3 g/kg diet) (PROE3). An increase in the final body weight “FBW”, bodyweight gain “BWG” and feed consumption was observed (P < 0.05) at different PROE levels. Also, the thymus and bursa percentages were increased in the PROE2 and PROE3 treatments (P < 0.05). The chicks fed on PROE supplemented diets had increased frequency of feeding, drinking, and showed comfortable behavior (P < 0.05) with lesser aggression (P < 0.05). Additionally, an increase was observed in the antioxidant enzyme activity, phagocytic %, phagocytic index, and lysozyme activity in PROE supplemented treatments, with the best outcome reported in the PROE3 treatment (P < 0.01). IgM was increased in the birds fed with PROE2 and PROE3 diets (P < 0.01). PROE supplementation increased the AID% of lysine and methionine (P <0.01), PROE3 treatment increased the AID% of threonine (P < 0.05), and PROE2 and PROE3 treatments increased the AID% of leucine and isoleucine (P < 0.05). Besides, PROE2 and PROE3 treatments increased the villus height and width, mucosal thickness, and goblet cell count from the duodena, jejuna, and ilea (P < 0.05). Based on these results, we concluded that the dietary addition of phenolic-rich onion extracts can improve the growth rate of broiler chicken by improving the AID% of amino acids and intestinal histology. Also, it can improve the welfare, antioxidant enzymes, and immune status of the birds. Phenolic-rich onion extracts can be used as a natural growth promoter in the poultry feed to better their performance and health.